The Balance between "Negative Liberty" and "Positive Liberty": -- On J.S.Mill’s Liberal Thought - You, Weining (Transactions on Social Science, Education and Humanities Research, 2024)
John Stuart Mill, a prominent figure in classical liberalism, inherits the emphasis on individual spirit from earlier liberals such as Locke. He expanded this notion to include social liberty on the basis of political liberty, deepening the public understanding of individual freedom. To some extent, Mill's recognition of negative liberty and human diversity also corrects the classical political philosophy's singular and universal natural purpose. Moreover, his proposal of positive standards and purposes, based on negative liberty, not only complements and corrects classical liberalism but also offers solutions to the problems arising from neoliberalism in the contemporary world.